The Generalized Uncertainty Principle and higher dimensions: Linking black holes and elementary particles - Carr, B. J. (Frontiers in Astronomy and Space Sciences, 2022)
Black holes play an important role in linking microphysics with macro- physics, with those of the Planck mass (MP ∼ 10−5g) featuring in any theory of quantum gravity. In particular, the Compton-Schwarzschild correspondence posits a smooth transition between the Compton wavelength (RC ∝ 1/M) below the Planck mass and the Schwarzschild radius (RS ∝ M) above it. The duality between RC and RS implies a form of the Generalized Uncertainty Principle (GUP) and suggests that elementary particles may be sub-Planckian black holes. The simplest possibility is that the ADM mass has the form M+βMP2/M for some constant β and this model can be extended to charged and rotating black holes, clearly relevant to elementary particles. Another possibility is that sub-Planckian black holes may arise in loop quantum gravity and this explicitly links black holes and elementary particles. Higher dimensions may modify both proposals. If there are n extra dimensions, all with the same compactification scale, one expects RS ∝ M1/(1+n) below this scale but RC depends on the form of the higher-dimensional wave-function. If it is spherically symmetric, then RC ∝ M−1, so duality is broken and the Planck mass is reduced, allowing the possibility of TeV quantum gravity. If the wave-function is pancaked in the extra dimensions, RC ∝ M−1/(1+n) and so duality is preserved but the Planck mass is unchanged.